Preferences of women with a vulnerable health status towards nudging for adequate pregnancy preparation as investment in health of future generations: a qualitative study - Sharissa M. Smith; Rianne M. J. J. van der Kleij; Babette Bais; Maartje H. N. Schermer; Hafez Ismaili M'hamdi; Régine P. M. Steegers-Theunissen (BMC, 2022)
Abstract Background Women with a vulnerable health status, as determined by a low socioeconomic status and poor lifestyle behaviours, are at risk for adverse pregnancy outcomes. Offering tailored preconception lifestyle care can significantly help to improve pregnancy outcomes. We hypothesize that so-called 'nudges' can be a successful way of increasing the uptake of preconception lifestyle care. A nudge is a behavioural intervention that supports healthy choices by making them easier to choose. Nudging, however, raises many moral questions. Effectiveness and respect for autonomy are, among other criteria, required for a nudge to be morally permissible. In general, the target group knows best what they find permissible and what would motivate them to change their lifestyle. Therefore, this study - conducted in women with a vulnerable health status - aimed to identify their preferences towards a nudge, provided via a mobile application that aims to help them adopt healthy lifestyle behaviours by offering rewards.  Methods We conducted semi-structured interviews with twelve women with a vulnerable health status. A framework approach was used to analyse the data. A thematic content analysis was conducted on five themes: (1) "Usefulness of an app as an integral information source", (2) "Permissibility and effects of offering rewards", (3) "Preferences regarding content", (4) "Preferences regarding type of rewards and system of allocation", and (5) "Barriers". Results Of the 12 participants, 11 deemed an app as integral information source concerning the preconception period useful. None of the participants objected to being nudged i.e., being rewarded for healthy behaviour. All participants stated that they would like the app to contain information on healthy nutrition and 8 participants wanted to know how to get pregnant quickly. Furthermore, participants stated that the freedom to choose the timing and content of the reward would increase the probability of successful behavioural change, and having to pay or contact a healthcare provider to access the app may prevent women using the app. Conclusions These insights into the preferences of women with a vulnerable health status towards nudging will inform the design of an effective app-based nudge. This may help to improve prepregnancy health as investment in health of current and future generations.